Comparison of UVC/S2O82- with UVC/H2O2 in terms of efficiency and cost for the removal of micropollutants from groundwater - Antoniou, Maria G.; Andersen, Henrik Rasmus (My University, 2015)
This study compared the UVC/S2O82- system with the more commonly used AOP in water industry, UVC/H2O2, and examined whether the first one can be an economically feasible alternative technology. Atrazine and 4 volatile compounds (methyl tert-butyl ether, cis-dichlorethen, 1,4-dioxane and 1,1,1-trichloroethane) were chosen as model contaminants because they exhibit different susceptibility to UVC photolysis and AOPs. A collimated beam apparatus was utilized for the majority of the experiments (controlled environment, without mass transfer phenomena), while selected experiments were performed in a flow-through reactor to simulate industrial applications. Initial experiments on the activation of oxidants with a LP lamp indicated that S2O82- is photolysed about 2.3times faster than H2O2 and that the applied treatment times were not sufficient to utilize the majority of the oxidant. The effect of oxidants' concentrations were tested with atrazine alone and in the micropollutants' mixture and it was decided to use 11.8mgL-1 S2O82- and 14.9mgL-1 H2O2 for further testing since is closer to industrial applications and to minimize the residual oxidant concentration. Changes of the matrix composition of the treated water were investigated with the addition of chloride, bicarbonate and humic acids at concentrations relevant to a well-water-sample, the results showed that the system least affected was UVC/H2O2. Only when bicarbonate was used, UVC/S2O82- performed better. Overall, testing these systems with the mixture of micropollutants gave better insights to their efficiency than atrazine alone and UVC/S2O82- is recommended for selective oxidation of challenging matrices.
Keywords: Collimated beam; Emerging contaminants; Flow-through reactor; Hydrogen peroxide; Persulfate; UVC